LANGUAGE ATTITUDES OF INDONESIANS AS EFL LEARNERS, GENDER, AND SOCIO-ECONOMIC STATUS - Paradewari, Dirtya Sunyi; Mbato, Concilianus Laos (LLT Journal: A Journal on Language and Language Teaching, 2018)
This study explored the language attitude in terms of gender and socio-economic status (SES) in Yogyakarta, Indonesia. The aim of this study was to find out the relationships among five components of languages attitudes in terms of gender and socio-economic status (SES). There were 256 participants from four universities in Yogyakarta. The participants were asked to fill out a questionnaire about the language used and general language attitudes through the Google Form. The results showed that there are five components of language attitudes; 1) Indonesian learners showed positive language attitudes toward English (3.58); 2) positive language attitudes toward Indonesian (3.66); 3) positive language attitudes toward English and negative language attitudes toward Indonesian (3.52); 4) positive language attitudes toward Indonesian and negative language attitudes toward English (3.58); 5) positive language attitudes toward English and Indonesian (3.91). These five components of language attitudes were then correlated with gender; 1) gender was positively related to English language attitude where female learners had higher positive language attitudes than males did toward English (.097); 2) there was no relation between gender and Indonesian language attitude (-.071). In addition, SES was also related to five (5) components of language attitudes in which the learners who came from upper class had higher positive language attitudes towards English (.155) than learners who came from lower class. On the other hand, the correlation between SES and Indonesian language showed the learners from middle class had higher positive language attitudes (.031) than the learners from upper class and lower class.